Methodological development of a wrestling shuttle test - Iwai, K.; Takahashi, R.; Yumoto, K.; Nakazato, K. (International Journal of Wrestling Science, 2018)
The purpose of this study was to develop a wrestling shuttle test (WST) based upon four elements. Firstly, the WST was conducted on a regulation wrestling mat surface making it specific and familiar to a competition area. It is convenient to administer in a typical wrestling venue by a coach or tester. Secondly, the WST included movements in four different directions across the entire mat surface including wrestling-specific standing movements (sidestepping). Thirdly, the test was based on the international match length consistent with United World Wrestling (UWW) rules of match duration of two three-minute periods of activity with a 30 second rest period. Lastly, the shuttle test focused on the individuality of the participant, that is, without a partner or others, to ensure results are solely of the participants` individual effort.